2021
DOI: 10.3389/feduc.2021.639814
|View full text |Cite
|
Sign up to set email alerts
|

Academic Integrity in Online Assessment: A Research Review

Abstract: This paper provides a review of current research on academic integrity in higher education, with a focus on its application to assessment practices in online courses. Understanding the types and causes of academic dishonesty can inform the suite of methods that might be used to most effectively promote academic integrity. Thus, the paper first addresses the question of why students engage in academically dishonest behaviours. Then, a review of current methods to reduce academically dishonest behaviours is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(103 citation statements)
references
References 52 publications
2
51
0
12
Order By: Relevance
“…From the didactic point of view, it is more valuable if the feedback provides not only a correct answer but also an explanation and, if the answer is not correct, also a source where the learner can study the topic again. If online tests are used for assessment, the value of the test result is higher, if teachers are sure that learners worked independently, without any dishonest behaviour (Holden et al, 2021 ; Noorbehbahani et al, 2022 ). As it has been detected worldwide, there exist numerous didactic recommendations how to minimize the opportunities of such behaviour (Nguyen et al, 2020 ; Dendir & Maxwell, 2020 ).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…From the didactic point of view, it is more valuable if the feedback provides not only a correct answer but also an explanation and, if the answer is not correct, also a source where the learner can study the topic again. If online tests are used for assessment, the value of the test result is higher, if teachers are sure that learners worked independently, without any dishonest behaviour (Holden et al, 2021 ; Noorbehbahani et al, 2022 ). As it has been detected worldwide, there exist numerous didactic recommendations how to minimize the opportunities of such behaviour (Nguyen et al, 2020 ; Dendir & Maxwell, 2020 ).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Students' ethical and moral integrity and values which could make them prone to cheating during online exams were not examined by this questionnaire. However, a research review of academic integrity in online assessment by Holden et al (2021) showed that both, students and faculty perceive online testing to offer more cheating opportunities than in traditional, liveproctored classroom environment.…”
Section: Discussionmentioning
confidence: 99%
“…Our robot is designed and trained to flag more suspicious behavior than ones based on face detection alone. Cheating detection using AI is possible and, while not standardized, has been shown to help [25,26].…”
Section: Analysis and Discussionmentioning
confidence: 99%